2005
DOI: 10.1073/pnas.0406380102
|View full text |Cite
|
Sign up to set email alerts
|

Neutral sphingomyelinase 2 ( smpd3 ) in the control of postnatal growth and development

Abstract: Neutral sphingomyelinases sphingomyelin phosphodiesterase (SMPD)2 and -3 hydrolyze sphingomyelin to phosphocholine and ceramide. smpd2 is expressed ubiquitously, and smpd3 is expressed predominantly in neurons of the CNS. Their activation and the functions of the released ceramides have been associated with signaling pathways in cell growth, differentiation, and apoptosis. However, these cellular responses remain poorly understood. Here we describe the generation and characterization of the smpd3 ؊/؊ and smpd2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
170
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(185 citation statements)
references
References 45 publications
8
170
2
5
Order By: Relevance
“…For example, although thorough longevity studies have yet to be performed, NSMase-2 knockout mice exhibit dwarfism and delayed puberty, which are indicators of delayed aging. 43 In D. melanogaster, mutation in the neutral ceramidase gene leads to increased cellular ceramide content and a rapid onset of aging-associated photoreceptor degeneration. 47 And lastly, but most importantly, convincing evidence for ceramide's involvement in the process of aging comes from studies in yeast, where the longevity assurance genes, LAG1 and LAC1, in yeast that participate in de novo ceramide biosynthesis, have been shown to determine yeast lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although thorough longevity studies have yet to be performed, NSMase-2 knockout mice exhibit dwarfism and delayed puberty, which are indicators of delayed aging. 43 In D. melanogaster, mutation in the neutral ceramidase gene leads to increased cellular ceramide content and a rapid onset of aging-associated photoreceptor degeneration. 47 And lastly, but most importantly, convincing evidence for ceramide's involvement in the process of aging comes from studies in yeast, where the longevity assurance genes, LAG1 and LAC1, in yeast that participate in de novo ceramide biosynthesis, have been shown to determine yeast lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…4E). This would imply 40%-80% inhibition of endogenous NSMase-2 activity based on the fact that according to recent studies 43 NSMase-2 accounts for approximately 25%-50% of the total Mg 2ϩ -dependent NSMase activity in liver, with the rest being attributed to NSMase-1, an enzyme that has no known role in cell signaling. Most significantly, NSMase-2 inhibition with siRNA enhanced IRAK-1 degradation on IL-1␤ treatment (Fig.…”
Section: Downregulation Of Nsmase Activity In Aged Hepatocytes Restormentioning
confidence: 99%
“…Bone deformities in mouse models lacking a functional Smpd3 (sphingomyelin phosphodiesterase 3) gene underscore the importance of sphingolipid metabolism in skeletal tissues (Aubin et al, 2005;Stoffel et al, 2005). Smpd3 encodes neutral sphingomyelinase 2 (nSMase2), a membrane-bound enzyme, which cleaves sphingomyelin to generate the lipid second messenger ceramide.…”
Section: The Fro Mutation Abolishes Nsmase2 Activity But Does Not Affmentioning
confidence: 99%
“…Furthermore, nSMase activity is enhanced by ionizing radiation (15,31), the DNAdamaging agents Adriamycin, daunorubicin, and etoposide (12,32,33), hypoxia (34), and UV radiation (35), although the relative contribution of specific nSMase enzymes in mediating the response to these stressors remains unclear. The creation of nSMase1 À/À and nSMase2 À/À mice has provided some insights into the functions of these enzymes (36,37); however, more studies are needed to fully examine the independent effects of each in cellular stress-induced ceramide generation and their role in tumorigenesis. Adding another layer to the complexity of ceramide metabolism, Krut et al (38) have very recently reported the identification of nSMase3 as a third neutral sphingomyelinase.…”
Section: Introductionmentioning
confidence: 99%